Heating and water services design in buildings - Moss, Keith (E & FN Spon, 1996)
Heating and Water Service Design in Buildings has been written following thirteen years in the industry and twenty seven years teaching and consultancy work. The author has worked with college students, university undergraduates and open learning candidates of all ages.